Synergistic action of praziquantel and host specific immune response against Schistosoma mansoni at different phases of infection Ação sinergística do praziquantel e resposta imune específica do hospedeiro ao Schistosoma mansoni em diferentes fases da infecção - Fabio Ribeiro; Rômulo Teixeira de Mello; Carlos Alberto Pereira Tavares; John Robert Kusel; Paulo Marcos Zech Coelho (Revista do Instituto de Medicina Tropical de São Paulo, 2004)
The interaction between specific immune response to Schistosoma mansoni and praziquantel (PZQ) was studied in mice. In mice harboring concomitant immunity, 6-day-old parasites treated with PZQ were more effectively removed than 24h treated parasites despite both had a significant worm burden reduction when compared with respective treated controls. These results show that PZQ can be effective at the skin and lung stages of parasite's development mainly acting with a established specific immune response, and particularly at the lung phase. A interação entre a resposta imune específica ao Schistosoma mansoni e praziquantel (PZQ) foi avaliada em modelo murino. Em camundongos portadores de imunidade concomitante, parasitos com 6 dias de idade e tratados com PZQ, foram eliminados mais eficazmente do que parasitos de apenas 24 h, apesar de ambos mostrarem uma redução significativa da carga parasitária quando comparados com os respectivos controles tratados. Estes resultados mostram que o PZQ pode ser eficaz nos estágios de pele e pulmão durante o desenvolvimento do parasita, agindo principalmente com uma resposta imune específica estabelecida e, particularmente, na fase pulmonar.